2019
DOI: 10.36490/journal-jps.com.v2i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Uji Aktivitas Antioksidan Ekstrak Etanol Fraksi Heksan, Fraksi Etil Asetat dan Fraksi Air Daun Kapulaga (Elettaria cardamomum (L.) Maton)

Abstract: Penelitian ini bertujuan untuk mengetahui aktivitas antioksidan ekstrak etanol, fraksi heksan, fraksi etil asetat dan fraksi air daun kapulaga (Elettaria cardamomum (L.) Maton). Simplisia daun kapulaga diekstraksi dengan cara maserasi dengan menggunakan pelarut etanol 70 %, kemudian dilanjutkan dengan fraksinasi berdasarkan tingkat kepolaran dengan pelarut heksan, etil asetat dan air. Pengujian aktivitas antioksidan dilakukan dengan metode DPPH menggunakan spektrofotometri UV-Vis dan asam galat sebagai pemband… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Winarsi et al (2013) explained that cardamom leaf extract could control blood glucose levels, which may be antiatherogenic in diabetic rats. In addition, Asra et al (2019) have tested the phytochemical and antioxidant activity of cardamom leaf extract showing that cardamom leaf extract contains phenolic compounds, flavonoids, tannins, and saponins and may have antioxidant activity. Tmušic et al (2021) reported that Melissa officinalis L. produced higher total phenolic content under shaded conditions than treatment without shade.…”
Section: Introductionmentioning
confidence: 99%
“…Winarsi et al (2013) explained that cardamom leaf extract could control blood glucose levels, which may be antiatherogenic in diabetic rats. In addition, Asra et al (2019) have tested the phytochemical and antioxidant activity of cardamom leaf extract showing that cardamom leaf extract contains phenolic compounds, flavonoids, tannins, and saponins and may have antioxidant activity. Tmušic et al (2021) reported that Melissa officinalis L. produced higher total phenolic content under shaded conditions than treatment without shade.…”
Section: Introductionmentioning
confidence: 99%
“…The DPPH method was chosen because it is a fast, simple antioxidant testing technique or method, and does not use many chemical reagents. The use of the DPPH method also requires only a small number of samples [18]. The IC50 value is the concentration value that results in 50% loss of DPPH activity.…”
Section: Resultsmentioning
confidence: 99%
“…9 Senyawa metabolit sekunder yang dimiliki kapulaga adalah saponin, flavonoid, tanin, dan fenol. 10 Kandungan yang dimiliki oleh kayu manis adalah flavonoid, fenolik, saponin, tanin, dan triterpenoid. 11 Kayu secang diketahui memiliki kandungan metabolit sekunder terpenoid, flavonoid, dan fenol.…”
Section: Pendahuluanunclassified